The Effect of Virtual Reality on Emotional Response and Symptoms Provocation in Patients With OCD: A Systematic Review and Meta-Analysis - Dehghan, Bahram; Saeidimehr, Saied; Sayyah, Mehdi; Rahim, Fakher (Frontiers in Psychiatry, 2022)
This systematic review and meta-analysis aimed to evaluate the effectiveness of VR-based technology on emotional response and symptoms in patients with obsessive-compulsive disorder (OCD). We systematically searched major electronic databases, including Pubmed/Medline, Scopus, Embase, ISI web of science, PsycINFO, and Cochrane central, up to 14 April 2021 with no data or language limits. We performed reference, related articles, and citation searches to find additional articles. We included original articles comparing and studying VR-based technology in patients with OCD against the control group. We observed that VR significantly increase in anxiety (SMD = 2.92; 95% CI 1.89–3.94, p < 0.0001; I2 =95%), disgust (SMD = 2.52; 95% CI 1.36–3.68, p < 0.0001; I2 =95%), urge to wash (SMD = 3.12; 95% CI 1.92–4.32, p < 0.0001; I2 =94%), checking time (SMD = 1.06; 95% CI 0.71–1.4, p < 0.0001; I2 =44%), number of checking behavior (SMD = 1.45; 95% CI 0.06–2.83, p =0.04; I2 =93%), and uncertainty (SMD = 2.59; 95% CI 0.90–4.27, p = 0.003; I2 =70%) in OCD patients compared with healthy controls using a random-effect model. This meta-analysis found that this environment has a moderate enhancement in emotional response and symptoms test scores of patients with OCD. However, our findings should be generalized with caution due to the lack of standardized methods and high heterogeneity among included evidence. The appropriate mode of integrating VR-based technology for patients with OCD requires more exploration.